Influência do defeito tipo cunha no comportamento mecânico de juntas de liga de alumínio 2198 soldadas por fricção por ponto (FSpW) - Barros, Pablo Aronne Funchal de (2015)
One of the main considerations in selecting materials to manufacture aircraft structures is related to weight saving [1]. In this context, the promising aluminum-lithium alloys have been receiving special attention in aerospace applications due to its attractive combination of low density, high specific strength and corrosion resistance [2-5]. Due to difficulties joining these alloys by conventional welding processes associated to their high thermal conductivity and low melting temperature, solid-state joining technologies emerge as great possibilities to simultaneously solve problems of solidification defects and increasing weight. The feasibility of Friction Spot Welding (FSpW) in joining sheets of lightweight material (e.g. aluminum alloys) places this technology as a potential replacement to the spot-like joint processes, as resistance spot welding (RSW) and laser spot welding (LSW), for application in automotive and aerospace industries [6-8]. In this work, the influence of hook defect on the lap shear strength (LSS) of AA2198-T8 friction spot welds was studied. The effects of process parameters was evaluated in terms of LSS and related to the microstructural configurations. The values of hook length measurements and the LSS were used as response in optimization process developed using the statistical tool of DoE technique with Taguchi Method. Finally it was possible to compare the hook behavior with lap shear strength results. The higher influence on the weld performance was exerted by plunge depth whereas rotational speed was found to be a less significant parameter. Through the minimization of the hook defect, a beneficial response on the weld performance was observed, which was associated to the absence of a potential site for crack nucleation. In spite of inherent discontinuities, promising results were found for aluminum joints for aerospace applications.